Fora da vida - Reis, Filipa; Miller Guerra, João (Portugal : Vende-se Filmes, 2015)
An investigation of Lisbon suburban life where some struggle to find work and others find it difficult to save time for leisure activities.
Verzio Film Festival Submission
Keywords: Documentary films